Analysis of Mothers' Knowledge on Initial Management of Febrile Seizure Emergencies in Toddlers at Home - Afrah Diba Faisal; Ira Suryanis; Epi Satria; Nirmala Sari; Hendri Devita (Jurnal Kesehatan Cendikia Jenius, 2026)
Febrile seizures are a common emergency in toddlers and carry the risk of complications if initial treatment at home is inadequate. Mothers' knowledge plays a crucial role in determining the first course of action when a child experiences a febrile seizure. This study aims to analyze mothers' knowledge regarding the initial emergency treatment of febrile seizures in toddlers at home. The study used a qualitative design with a descriptive phenomenological approach. Data were collected through in-depth interviews using a semi-structured guide with 12 mothers with toddlers with a history of febrile seizures in the Alai Community Health Center, Padang City, selected using purposive sampling. Data analysis was conducted thematically. The results revealed two main themes: not knowing what to do and doing whatever comes to mind. The first theme describes mothers' panic and lack of knowledge in dealing with febrile seizures, while the second theme reflects spontaneous actions taken by mothers, including taking the child to a health facility or performing other treatments that do not fully meet standards. This study concluded that mothers' limited knowledge and panic influence the inaccuracy of initial treatment of febrile seizures. Therefore, improved health education for families is needed to improve preparedness and appropriate treatment of febrile seizures in toddlers